‘Monk’ Lewis’ “The Isle of Devils” and the Perils of Colonialism - Nevárez, Lisa (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractThis essay focuses on Matthew “Monk” Lewis’ poem “The Isle of Devils,” which appears in his Journal of a West India Proprietor. The poem relates the story of a shipwrecked woman, Irza, who finds herself at the mercy of a “Fiend” on an unnamed island that lies somewhere off the coast of Africa. With an analysis of the splitting of binaries such as colonizer/colonized, fertility/barrenness, mothering/murder, and poison/antidote/pharmakon contained in the poem, this essay investigates the dynamics of colonization. I discuss miscegenation and hybridity in connection with the Fiend and Irza’s children, who perish at the hands of the father following the mother’s abandonment of her family, and in the context of Lewis’ Journal. By way of a Derridean approach, the seemingly contradictory action of healing/harming in the poem gives way to a reading of the Fiend and Irza as equally to blame for the bloody demise of their island family, and one can call into question who—and what—is “monstrous.”